TINGKAT LAYANAN TRANSPORTASI LRT (AREA AMPERA DAN BANDARA SMB II) PERPINDAHAN MODA ANGKUTAN - Royan, Noto; Setiawati, Mira; Febriyanto, Miko (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2021)
Public transportation is a very important field of activity in the life of the Indonesian people, especially in Palembang City, the capital city of South Sumatra. The existence of good transportation services will be able to reduce people's dependence on the use of private vehicles and reduce congestion in the city of Palembang. One aspect of transportation that concerns the needs of many people is public transportation, such as LRT (Light Rail Transit), Trans Musi Bus, Water Bus and City transport. Currently, service levels or occupancy levels are not yet a priority.The type of research used by the author in this study is descriptive qualitative. Data collection techniques are interviews, observation, and documents related to research.Based on the data analysis carried out, it is concluded that the largest number of vehicle transfers between modes of transportation is from others (private cars, private motorbikes, pedicabs, walking and motorbikes) - as many as 52 passengers. Furthermore, from the City transport - LRT as many as 39 passengers. Furthermore, from City transport - Trans Musi as many as 37 passengers. Furthermore, from LRT - Trans Musi as many as 33 passengers.Keywords: Service level, occupancy, transportation, mode shift of public transportation